Triggering receptors expressed on myeloid cells (TREM) - McVicar, Daniel W. (Henry Stewart Talks, 2013)
TREM-Discovery, Genomic organization and expression-TREM-Like Transcripts (TLT), 6-TREM-like Transcript-4 (TREML4) in antigen capture and processing, TREM-like Transcript (TLT) 2 in neutrophil and T cell regulation, TREM-like Transcript (TLT) 1 in platelet regulation, TREM-1 in inflammatory disease and cancer, TREM-2 in dendritic cell, preOsteoclast and macrophage regulation